Islamic Corporate Governance (ICG) On Sharia Financial Performance with Islamic Social Reporting (ISR) As A Moderating Variable - Chairil Afandy; Berto Usman; Intan Zoraya (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of Islamic Corporate Governance (ICG) on Financial Performance with Islamic Social Resporting (ISR) as a Moderating Variable in Islamic Commercial Banks in Indonesia for the 2018-2020 period. The sample of this study was determined by purposive sampling method with criteria determined by the researcher, the analytical method used was multiple linear regression analysis with Moderated Regression Analysis (MRA) test using Eviews 10 data processing software. The results showed that the variables Number of Board of Commissioners, Number of Number of Audit Committees, Number of Board of Directors and Number of DPS had a positive and significant effect on Islamic Financial Performance. Sharia Finance, ISR cannot moderate the influence of the Number of Board of Directors on Sharia Financial Performance, ISR can moderate (strengthen) the influence of the Number of Audit Committees on Sharia Financial Performance, ISR cannot moderate the influence of the Number of Board of Directors on Sharia Financial Performance.